Clinical Status and Idea Analysis of Long Needle Penetration Acupuncture in the Treatment of Stroke Sequelae - Luo, Dan; Zhao, Weifeng; Zhu, Jieyu; Yang, Xinyi; Cao, Shizhuang (Journal of Contemporary Medical Practice, 2025)
Stroke is an acute cerebrovascular disease with a rapid onset. After a stroke, most patients suffer from motor, sensory, or cognitive impairments of varying degrees, lose their ability to live independently, and their quality of life is seriously affected. This has become a clinical problem that urgently needs to be addressed. Starting from the origin and characteristics of the long needle penetration acupuncture method, this article reviews relevant domestic and international literature, summarizes the current status of long needle penetration acupuncture in the treatment of stroke sequelae, analyzes its treatment ideas, and provides relevant references for clinical practice.